Computation of Interactional Forces Between Two Submerged Bodies in an Overtaking Maneuver (Advances in Applied Mathematics and Mechanics, 2020)
When two overtaking bodies sail in close proximity, the additional sway force and yaw moment will be induced due to the changed relative velocity in the narrow clearance between them, which directly affect their course keeping. Up till now, the extensive data about the related body-to-body interaction effects are typically obtained from the captive model tests or the computational fluid dynamics (CFD) based calculations for the model fixed condition. In this work, the objective is to study the viscous hydrodynamic forces between two overtaking bodies for the model free condition. By coupling the incompressible Reynolds-averaged Navier-Stokes (RANS) equations and the motion equations of the two bodies, the complicated multi-degree of freedom motions in surge, sway and yaw are simulated. The detailed flow field characteristics, motion parameters including motion trajectories and yaw angles, and the viscous hydrodynamic forces acting on two bodies are procured. The effects of relative speed and various lateral distances are investigated to elucidate their influences on the interactional forces. The flow features at different time instants and the bodies' trajectories shown in the present article are helpful for the navigator to understand the mechanism of body-to-body collision accident.